The Effect of Bleaching Agents on the Microstructure and Surface Microhardness of Three Calcium Silicate-based Barrier Materials - Meraji, Naghmeh; Ahmadi, Elham (Iranian Endodontic Journal, 2020)
Introduction: The aim of this study was to evaluate the effects of exposure to sodium perborate and H2O2 on the surface characteristics of MTA Angelus, Biodentine and MTA Repair HP after 1 and 6 month time intervals. Methods and Materials: Three calcium silicate-based cements were evaluated: MTA Angelus, Biodentine, MTA Repair HP. A total of 234 specimens were stored in Hank’s balanced salt solution (HBSS) for 1 month or 6 months in which afterwards were divided into 3 groups according to bleaching agent applied: control, sodium perborate, 35% hydrogen peroxide. The microstructural changes were evaluated by scanning electron microscopy and energy-dispersive X-ray spectroscopy. The surface microhardness was also evaluated. Data were analyzed by one-way analysis of variance and Games-Howell post-hoc tests for the effect bleaching agents and hydraulic calcium silicate-based cements and t-test was for the effect of time. Results: Distinctive alterations with uneven depression areas, woodpecker defects and cracks were seen due to exposure to perborate and H2O2 on all evaluated cements. Exposure to H2O2 caused a decrease in Ca/Si ratio in all experimental cements. Both H2O2 and perborate significantly decreased the microhardness of all cement (P<0.05) with H2O2 having a more profound effect (P<0.01). A 6-month delay in exposure to bleaching agents significantly increased the microhardness of Biodentine compared to 1 month (P<0.001 for both bleaching agents). Conclusion: Based on this in vitro study, H2O2 had more detrimental effects on MTA Angelus, Biodentine and MTA Repair HP. Sodium perborate may be a more conservative selection when considering effects on barrier materials. Keywords: Bleaching Agent; Calcium Silicate Cement; Microhardness; Mineral Trioxide Aggregate; Scanning Electron Microscopy